Study on finite element analysis of the external heat resistance of cables in ductbank - Jian Wang; Huan Jin; Zhi Yang; Bin Zhao; Xiao Ma; Kunpeng Ji (Energy Reports, 2020)
Power cable engineering is a critical method for urban power supply, and ductbank laying of cables is a way of underground cable lines. Considering the cost and construction, MPP pipes with poor heat dissipation performance are often used in ductbank. Many cables are arranged densely in the piping group, which reduces the ampacity of cable lines. According to the formula for calculating the ampacity in IEC60287 standard, the external thermal resistance of cable is affected by the laying environment, which is an important factor affecting the ampacity of cable. However, calculation method for the external thermal resistance of directly buried cable and cable laid in air is given in the standard merely, while the external thermal resistance of cable laid in ductbank is not given for each hole. In this paper, using the definition formula of external thermal resistance and finite element analysis method, the thermal resistance of each hole of ductbank is studied, and the external thermal resistance of the ductbank is obtained accurately, which is conducive to the analysis of the ampacity of cable and the rational arrangement of the cable laying hole position.
Keywords: 330; Cable ampacity; Cable ductbank laying; Equivalent thermal resistance; Finite element method